QUANTIFICATION OF ASTAXANTHIN PRODUCTION BY Haematococcus pluvialis INDUCED BY COPPPER NANOPARTICLES - Thinakren, Batumalai (2018)
Haematococcus pluvialis is green microalgae that is found in harsh-free regions like Africa, Europe and North America. It has the ability to produce high yield of astaxanthin under stress as such as when exposed to high temperature, pH, salinity, light and nitrogen deficiency. Astaxanthin is an unsaturated antioxidant that can also be found in various marine animals and microorganism. Astaxanthin were produced under stress condition. The aim of this study is to (i) develop H. pluvialis culture and (ii) investigate the effect of Cu nanoparticles to the production of astaxanthin in H. pluvialis. The H. pluvialis cells were grown in laboratory condition using circadian light, plus their growth patterns and cell count were measured using cell count chamber and light microscope and further analysed under 470 nm in the spectrophotometer in every 2 -3 days. The H. pluvialis cells were induced with different concentration of Cu nanoparticle at 100 mg/L, 200 mg/L and 300 mg/L. The astaxanthin were extracted and quantified at 470 nm using a spectrophotometer in every 4 - 5 days. The data were statistically analyzed using simple tools in Microsoft Excel 2016. Copper nanoparticles cannot enhance the production of astaxanthin in H. pluvialis due to high toxic level.